2013
DOI: 10.1371/journal.pone.0063524
|View full text |Cite
|
Sign up to set email alerts
|

Reforestation Sites Show Similar and Nested AMF Communities to an Adjacent Pristine Forest in a Tropical Mountain Area of South Ecuador

Abstract: Arbuscular mycorrhizae are important for growth and survival of tropical trees. We studied the community of arbuscular mycorrhizal fungi in a tropical mountain rain forest and in neighbouring reforestation plots in the area of Reserva Biológica San Francisco (South Ecuador). The arbuscular mycorrhizal fungi were analysed with molecular methods sequencing part of the 18 S rDNA. The sequences were classified as Operational Taxonomic Units (OTUs). We found high fungal species richness with OTUs belonging to Glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 60 publications
2
24
0
1
Order By: Relevance
“…Among the abiotic factors that can have relevant roles in driving AMF communities are soil moisture (75), rainfall patterns, and geographical distance (40,76). There is no doubt that soil type has a role in the AMF distribution (10,34,35,40,(77)(78)(79)(80), and our work also demonstrated that soil type is a major factor driving AMF assemblages, after elimination of the host factor and other environmental variables not related to soil characteristics. Although individual soil characteristics have been reported to play important roles in AMF community structure and composition (7,11,13,40,42,78,(81)(82)(83), very limited data sets regarding soil characteristics were used in these studies, and the relative incidences of each soil property determined after complete soil characterization have not been reported previously.…”
Section: Discussionsupporting
confidence: 55%
“…Among the abiotic factors that can have relevant roles in driving AMF communities are soil moisture (75), rainfall patterns, and geographical distance (40,76). There is no doubt that soil type has a role in the AMF distribution (10,34,35,40,(77)(78)(79)(80), and our work also demonstrated that soil type is a major factor driving AMF assemblages, after elimination of the host factor and other environmental variables not related to soil characteristics. Although individual soil characteristics have been reported to play important roles in AMF community structure and composition (7,11,13,40,42,78,(81)(82)(83), very limited data sets regarding soil characteristics were used in these studies, and the relative incidences of each soil property determined after complete soil characterization have not been reported previously.…”
Section: Discussionsupporting
confidence: 55%
“…However, the relationship between diversity of both partners of mycorrhizal communities is surely more complex. For example, replacing tree species rich pristine tropical forests by assemblages of lowered tree diversity had no real impact on the diversity of the mycobionts (Haug et al, 2013), which suggests that other factors than phytobiont diversity impact on mycobiont diversity, or that propagule banks provide a kind of resilience.…”
Section: Recruitment and Diversity Dynamics Of Mycobionts In Plant Comentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) community changes following nutrient additions might strongly affect a system that is characterized by high diversity, since high species richness may point to more intense specialization (Johnson & Steiner, 2000;Wright, 2002) and functional redundancy among species cannot be directly assumed (van der Heijden et al, 1998;Lyons et al, 2005;Isbell et al, 2011). A steep increase in diversity toward the tropics, as described for plants (Myers et al, 2000), has not been shown for AMF to the same extent.…”
Section: Introductionmentioning
confidence: 99%
“…As part of NUMEX, we evaluated the effects of N and P additions on AMF at the stand scale. We hypothesize based on findings of previous experiments and the assumption of a tropical forest characterized by N and P colimitation (Wullaert et al, 2010;Homeier et al, 2012) that (i) additions of N and P will decrease AMF abundance; (ii) nutrient additions will decrease AMF richness, with strong impacts on a community most likely characterized by high species richness, as might be revealed by 454-sequencing ( € Opik et al, 2009;Haug et al, 2013); (iii) a shift toward AMF lineages previously shown to be favored by fertilization will occur (Egerton-Warburton et al, 2007;Alguacil et al, 2010), since AM fungal species are known to differ in morphological traits (Maherali & Klironomos, 2012), soil demands (Johnson, 1993;Lekberg et al, 2007;Guo et al, 2012), and nutrient uptake strategies (Munkvold et al, 2004;Powell et al, 2009;Kiers et al, 2011). We analyzed intraradical AMF abundance as well as the intraradical community structure to obtain a comprehensive picture of potential effects.…”
Section: Introductionmentioning
confidence: 99%